PERAN PERHIMPUNAN PROFESI DALAM PERLINDUNGAN HUKUM BAGI TENAGA MEDIS DI INDONESIA - Miya Maryani, Ayu; Widjaja, Gunawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Professional associations play a crucial role in providing legal protection for medical personnel in Indonesia. Through various initiatives, including legal support, advocacy, and education on legal rights and obligations, professional associations help medical personnel face legal challenges and the risk of malpractice. In addition, professional associations play a role in maintaining standards of professionalism and quality of medical services by encouraging continuing education and implementing strict codes of ethics and standards of practice. Therefore, the existence of professional associations provides a sense of security and confidence for medical personnel, enabling them to focus on providing optimal health services to the community.